Characterization of Purple Acid Phosphatase Family and Functional Analysis of GmPAP7a/7b Involved in Extracellular ATP Utilization in Soybean - Zhu, Shengnan; Chen, Minhui; Liang, Cuiyue; Xue, Yingbin; Lin, Shuling; Tian, Jiang (Frontiers in Plant Science, 2020)
Low phosphate (Pi) availability limits crop growth and yield on acid soils. Although root-associated acid phosphatases (APases) play an important role in extracellular organic phosphorus (P) utilization, they remain poorly studied in soybean (Glycine max), an important legume crop. In this study, dynamic changes in intracellular (leaf and root) and root-associated APase activities were investigated under both Pi-sufficient and Pi-deficient conditions. Moreover, genome-wide identification of members of the purple acid phosphatase (PAP) family, and their expression patterns in response to Pi starvation were analyzed in soybean. The functions of both GmPAP7a and GmPAP7b, whose expression is up-regulated by Pi starvation, were subsequently characterized. Phosphate starvation resulted in significant increases in intracellular APase activities in the leaves after 4 d, and in root intracellular and associated APase activities after 1 d, but constant increases were observed only for root intracellular and associated APase activities during 5 to 16 d of P deficiency in soybean. Moreover, a total of 38 GmPAP members were identified in the soybean genome. The transcripts of 19 GmPAP members in the leaves and 17 in the roots were up-regulated at 16 d of P deficiency despite no response for any GmPAP members to Pi starvation at 2 d. Pi starvation up-regulated GmPAP7a and GmPAP7b were subsequently selected for further analysis. Both GmPAP7a and GmPAP7b exhibited relatively high activities against adenosine triphosphate (ATP) in vitro. Furthermore, overexpressing GmPAP7a and GmPAP7b in soybean hairy roots significantly increased root-associated APase activities, and thus facilitated extracellular ATP utilization. Taken together, these results suggest that GmPAP7a and GmPAP7b might contribute to root-associated APase activities, and thus function in extracellular ATP utilization in soybean.